Across the universe - Revis, Beth (New York : Razorbill, 2012)
Teenager Amy, a cryogenically frozen passenger on the spaceship Godspeed, wakes up to discover that someone may have tried to murder her.
Keywords: Interplanetary voyages -- Fiction; Science fiction